Diagnostic study about the labor market insertion of the 2019 graduates of the Bachelor of Arts in English Teaching of the Foreign Language Department of the school of Arts and Sciences of The University of El Salvador. - Guerrero Martínez, Sara Noemi; Lunas Vásquez, Karen Vanessa; Portillo Guillen, Mirella Astrid (2024)
This report synthesizes the main findings of the research which are the fields where graduates have been inserted in the labor market in our country after they graduated, the results are based on the census of graduates of the 2019 year. This research was developed with the help of many important components such as instrument , resources and the contribution from the population that was able to participate and got involved in it so that the team can gather information in which they could give us their own opinions in references of the real exigencies that the labor market demands in an English environment at the moment of applying for a job opportunity, as a result, the team concluded that all graduates are capable of getting inserted in different fields for example: call center industry which is now the one that is most accessible for graduates ,they are also capable in the tourism field as well as in translation and interpretation and all this according to the latest requirements of the labor market. Key Words: Labor market ; Demands ; Call center ; Translation ; Tourism ; Interpretation.